Pelatihan Industri Kecil dan Menengah Pengembangan Produk Pengolahan Pangan di Kota Kendari - La Ode Muh Fitrah Arsyad; Ayuningtyas Putri Mumpuni H Asy'Ary; Astriwati Astriwati; Arfin Bagea; Muh. Yasin (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2024)
This training program aims to improve the ability of Small and Medium Industries (SMEs) in Kendari City to develop food processing products. The method used in implementing the program is a participatory approach to the community, where training participants are actively involved in every stage of the activity, from identifying needs to implementation and evaluation. This approach ensures that training materials are tailored to the specific needs of participants, and encourages a sense of ownership of the training results. The results of this program indicate that the main objectives of the training have been achieved well. Participants showed significant improvements in food processing knowledge and skills. The products produced after the training showed improved quality, both in terms of product safety and market appeal. An important lesson learned is the importance of tailoring training content to the specific needs of participants, as well as providing post-training assistance to ensure effective application of knowledge in their businesses. As a follow-up, it is recommended to hold more in-depth follow-up training, especially in the areas of digital marketing strategies and modern packaging techniques. Additional support in the form of access to technology and production equipment is also needed to expand the impact of this training. With ongoing training and post-program support, SMEs in Kendari City are expected to continue to develop their products and increase competitiveness in an increasingly competitive market